Multi-objective optimization of the honeycomb core in a honeycomb structure using uniform design and grey relational analysis. Issue 2 (1st February 2022) - Cheng, Yung-Chang; Yeh, Huai-Chun; Lee, Cheng-Kang
Abstract : This study increases the strength of a honeycomb structure under a static load using an innovative and integrated multi-objective optimization procedure. Using a uniform design of experiment, a group of simulation experiments is generated. Finite-element analysis is utilized to determine the maximum von Mises stresses in the honeycomb core for three ASTM testing simulations. Kriging interpolation is used to produce three surrogate models that correspond to the three maximum von Mises stresses using the results of the simulation experiments in the uniform design. To allow three maximum von Mises stresses be reduced simultaneously, grey relational analysis, entropy weighting analysis and a genetic algorithm are used to resolve this multi-objective optimization problem. Compared with the original design, the optimal design induces 5.07, 17.31 and 10.54% improvements for ASTM C297, C364 and C365 testing simulations, respectively. Consequently, the integrated multi-objective optimization technique produces a stronger honeycomb core in the honeycomb structure.